Validity and reliability of new equations for the prediction of maximal oxygen uptake in male and female elite adolescent rowers - Cherouveim, E. D.; Methenitis, S. K.; Simeonidis, T.; Georginis, P.; Tsekouras, Y. E.; Biskitzi, C.; Tsolakis, C.; Koulouvaris, P. (Journal of Human Kinetics, 2022)
The aim of this study was to develop accurate, reliable, and reproductive equations for the prediction of maximum oxygen uptake (VO2max) in male and female high-level adolescent rowers. This study included two parts. In the first part, VO2max was evaluated in 106 male and 83 female high-level adolescent rowers during an incremental step test (IRT) on a rowing ergometer, and stepwise multiple regression analyses were used for the development of new equations. In the second part, these equations were tested in 26 new high-level adolescent rowers of the same age and anthropometrical characteristics (boys: 15.27 ± 2.70 yrs and 15.34 ± 2.80 yrs; 72.37 ± 10.96 kg and 70.96 ± 10.65 kg; girls: 15.00 ± 2.11 yrs and 15.94 ± 2.71 yrs; 62.50 ± 7.14 kg and 63.41 ± 6.72 kg for parts 1 and 2, respectively; p > 0.05). VO2max was predicted from the combination of lean body mass (LBM) and the distance covered during the last 4 min stage of the IRT (boys: r 2 = 0.715, F = 68.74, p = 0.001; girls: r2 = 0.769, F = 57.81, p = 0.001). In the second part, no significant differences were identified when the new equations were tested against measured VO2max (boys: 3971.15 ± 713.38 mL·min-1 vs. 3915.83 ± 704.43 mL·min-1; girls: 3272.75 ± 551.46 mL·min-1 vs. 3308.94 ± 557.59 mL·min-1 for measured and predicted values, respectively; p > 0.05). In conclusion, VO2max of high-level adolescent rowers can be predicted with high accuracy, reliability, and repeatability using simple and easily evaluated anthropometric and performance variables.